Study of “quantum + classical” wavelength division multiplexing technique in optical network - Yi QIAN; Xiangyu LIN; Dong WANG; Xiaobao HU; Jinjian CHEN; Wenhao CHEN (Dianxin kexue)
The co-propagation of quantum key distribution (QKD) and classical optical communication via wavelength division multiplexing (WDM) was studied,based on 40 MHz system clock decoy BB84 QKD.In the bi-directional CWDM scheme,1.2 kbit/s key generation rate was achieved while the quantum wavelength (1 550.12 nm) ,synchronization wavelength (1 310 nm),forward direction error-free 100 Mbit/s data wavelength (1 590 nm) and backward direction error-free 100 Mbit/s data wavelength (1 610 nm) were multiplexed over 70 km fiber.In the dual-fiber unidirectional CWDM scheme,1.58 kbit/s key generation rate was achieved while the quantum wavelength (1 550.12 nm),synchronization wavelength (1 610 nm) and forward direction error-free 10 Gbit/s data wavelength (1 310 nm) were multiplexed over 55 km fiber.In the dual-fiber unidirectional DWDM scheme,1.16 kbit/s key generation rate was achieved while the quantum wavelength (1 550.12 nm),synchronization wavelength (1 610 nm) and two forward direction error-free 100 Gbit/s DP-QPSK data wavelength (emulated,1 551.72 nm and 1 552.52 nm) were multiplexed over 70 km fiber.